Comparison of Profitability of Listed Pharmaceutical Companies of Bangladesh - Mouri, D.; Suman, D.; Sujan, K.B. (My University, 2013)
Abstract Pharmaceutical industry is technologically the most advanced manufacturing industry in Bangladesh and the third largest industry in terms of contribution to government's revenue. The industry contributes about 1% of the total GDP. There are about 250 licensed pharmaceutical companies in Bangladesh. Currently a little over 100 companies are in production. According to IMS, a US-based market research firm, the retail market size is about BDT 84 billion as on 2011. Based on IMS report for the fourth quarter 2011, Square pharmaceutical holds the top market share in the retail market (18.7%), followed by Incepta and Beximco pharmaceutical. This sector fulfills 97% of the local medicine requirement. Besides, it is exporting chemicals and pharmaceutical products to global market including European market. The professional think tank, quality management, innovative ideas, government support are the key factors for the development of this sector. Hence the present study reports the profitability of two listed pharmaceutical companies of four year accounting period from 2008 to 2011. The analysis shows that average profitability indicators for Square are higher than Beximco, except gross profit ratio and operating profit ratio. On the other hand, the six other profitability indicators of Square are much higher than that of Beximco and go with the industry norm. Beximco has not been able to attain industry average net profit ratio, return on investment and return on equity, cash flow margin and cash return on assets.
Keywords: Profit; Profitability Indicators; Square And Beximco Pharmaceutical Industry